PP.30.19: WAIST CIRCUMFERENCE IS ASSOCIATED WITH SUBCLINICAL CARDIAC DAMAGE AMONG PATIENTS AFFECTED BY CHRONIC KIDNEY DISEASE. (June 2015) - Vettoretti, S.; Floreani, R.; Alfieri, C.; Meazza, R.; Barretta, F.; Lombardi, F.; Messa, P.
Abstract : Objective: Chronic kidney disease (CKD) is associated with a high cardiovascular (CV) morbidity and mortality. Early detection of subclinical cardiac damage(SCD) may help to prevent clinical events. In our study we investigated what clinical features are best associated with SCD in CKD patients without previous CV events. Design and method: 206 CKD patients(stages 1–4) were evaluated for: presence and duration of hypertension and diabetes mellitus(DM). We measured: blood pressure(BP), height, body weight, waist circumference(WC). We collected blood and 24 h urine samples to assess eGFR(CKD EPI), serum lipids, hemoglobin, phosphate, glucose, C-reactive protein(CRP), urinary albumin/creatinine ratio(ACR), 24 h urinary proteins, sodium and urea excretions. Left ventricular hypertrophy(LVH)was defined as left ventricular mass index(LVMI) > 51 g/m^2.7 and it was evaluated by echocardiography. The association between clinical parameters and LVMI were tested by uni and multivariate analyses. After that, ROC-curves were performed. Results: Mean age was 62 ± 14 years, males = 66%, eGFR 56 ± 31 ml/min, hypertension and DM were found in 87% and 46% resp. In 45%LVH was found. LVH correlated with female sex (k2 = 5, 1;p = 0, 0239), presence of DM(k2 = 6, 46;p = 0, 011), attainment of BP target < 140/90mmHg k2 = 5, 54;p = 0, 0186), age(p = 0, 0001), WC(p = 0, 0001), systolic BP (p = 0, 0001), diastolic BP(p = 0, 011), number of anti-hypertensive drugs (p = 0, 006), serum glucose (p = 0, 0007), HDL cholesterol (p = 0, 0003), triglycerides (p = 0, 0010), CRP (p = 0, 006). No correlations with renal function were found. Among all the parameters associated with LVH only WC showed a statistically association(p < 0.0001) in multivariate regression. WC- ROC AUC was 0.76 for males and 0.88 for females, indicating a good overall accuracy. After splitting our cohort in obese (defined by WC > 102 cm for men and > 88 cm for women) and non-obese individuals, obese had a higher prevalence of LVH (59 vs 24%; p = 0, 0001) as well as higher prevalence of DM (53 vs 33 %; p = 0, 0076), higher levels of systolic BP(142 ± 19 vs 133 ± 24; p = 0, 0022), poorer BP control (SBP/DBP > 140/90 mmHg; 48 vs 34%; p = 0, 045) and was prescribed a higher number of anti-hypertensive drugs (4, 8vs3, 2; p = 0, 003). Conclusions: Our data indicate that in CKD patients measurement of WC is an inexpensive tool to detect those patients with a worse metabolic profile and that should be further investigated for the presence of SCD.